Pharmacologic properties of high-dose ambroxol in four patients with Gaucher disease and myoclonic epilepsy. Issue 2 (24th October 2019) - Kim, Yoon-Myung; Yum, Mi-Sun; Heo, Sun Hee; Kim, Taeho; Jin, Hee Kyung; Bae, Jae-sung; Seo, Go Hun; Oh, Arum; Yoon, Hee Mang; Lim, Hyun Taek; Kim, Hyo-Won; Ko, Tae-Sung; et al.
Abstract : Background: Ambroxol (ABX) has been suggested as an augmentative pharmacological agent for neuronopathic Gaucher disease (nGD). This study assessed the long-term safety and efficacy of combined therapy with high-dose ABX and enzyme replacement therapy (ERT) in nGD. Methods: ABX+ERT therapy was administered for 4.5 years in four patients with nGD. ABX was initiated at a dose of 1.5 mg/kg/day, and the dose was escalated up to 27 mg/kg/day. The target plasma level was 10 µmol/L or less. The changes in glucocerebrosidase activity, biochemical, safety and neurocognitive findings were assessed. Results: Enhanced residual GCcase activity was observed in all patients, as evidenced in both in vitro and in vivo studies. During the first 2 years of study with ABX (up to 21 mg/kg/day), mean seizure frequencies and neurocognitive function worsened. After ABX dosage was increased up to 27 mg/kg/day of ABX, its trough plasma concentration was 3.2–8.8 µmol/L. Drug-to-drug interaction, especially with antiepileptic drug significantly affected the pharmacokinetic parameters of ABX. Importantly, at 27 mg/kg/day of ABX, the seizure frequencies markedly decreased from the baseline, and the neurocognitive function was improved. In addition, Lyso-Gb1, a biomarker for the severity and progression of GD, was normalised in all patients. High-dose ABX was well-tolerated with no severe adverse events. Conclusions: Long-term treatment with high-dose ABX+ERT was safe and might help to arrest the progression of the neurological manifestations in GD.